ENTITIES PERFORMING SELF-GOVERNMENT PUBLIC TASKS - SPECIFICITY OF ACTING AND FUNDING - Anna Milewska (Polityki Europejskie, Finanse i Marketing)
The goal of this article was to identify and characterize entities that participate in the process of performing public tasks. It contains their types and method of financial and/or organizational relationship with the budget of the municipal self-government. The article uses the methods of analysis and literature review as well as inductive and deductive reasoning. Institutional documents of a normative nature regarding the principles of self-government functions and literature on public (local) finances were used for the conducted research. The results show that functionally, the relationships between municipal companies and a commune budget can lead to disruptions in the assessment of the state of indebtedness of a local government entity. Following the experience of Great Britain, it can be concluded that one of the rational possibilities for carrying out projects is through a Public-Private Partnership. However, this solution can also bring financial dangers. Incorrectly dividing risks may lead to postponements of project performance or an excessive financial burden on the local government. It should also be noted that the private capital involvement formula (PPP contracts) can be used when there are economic benefits in the implementation of a specific public project, the scale of which may be of interest to the owners of capital. A significant number of public projects that are carried out by municipalities, especially in smaller (rural) entities, are in short supply and, in principle, do not give such an opportunity.